The Use of Electricity by Young Adults in Poland and Their Other Pro-environmental Behaviours – Case Study of the AGH Faculty of Management - Robert LISOWSKI; Anita PROSZOWSKA; Maciej WOZNIAK (Communications of International Proceedings, 2021)
The purpose of this article is to describe selected behaviors of young adults studying at AGH UST in the area of their use of electricity, water, waste segregation and decisions related to the choice of employer and to examine whether there are dependencies between them. The starting point of this study is a presentation of the state of the Polish economy in the areas covered by the survey. It is based on the analysis of reports of institutions monitoring the functioning of these branches of the economy. The characteristics of the current situation occupy a critical place among the analysed external data. The article also describes the research of young adults carried out for the needs of this work, the results obtained and the conclusions. The research took the form of a case study of students of the Faculty of Management of the AGH University of Science and Technology in Krakow supplemented by questionnaire surveys (on-line) of this group. The targeted choice is justified by the availability of respondents and their unique demographic-behavioural characteristics. The most important findings include the fact that most young adults consider their lifestyle to be environmentally friendly. At the same time, the primary impulse for pro-environmental behaviour is economic factors. In addition, consumers, especially men, seek to maximise the usefulness of their resources, especially when using electricity and, to a lesser extent, water. It was established that the increase in social involvement in pro-environmental activities depends not only on the will of the individuals but also on the number of external factors (including government support).
Keywords: Electricity; Pro-Environmental Behavior; Young Adults.